Conversion therapy from unresectable stage IIIC non-small-cell lung cancer to radical surgery via anti-PD-1 immunotherapy combined with chemotherapy and anti-angiogenesis: A case report and literature review - Jia, Guohua; Zhou, Shuimei; Xu, Tangpeng; Huang, Yabing; Li, Xiangpan (Frontiers in Oncology, 2022)
The prognosis of patients with stage IIIC non-small-cell lung cancer (NSCLC) is poor due to the loss of surgical treatment opportunities. Improving the prognosis of these patients with IIIC NSCLC urgently needs to be addressed. Here, we report a stage IIIC (T4N3M0 IIIC (AJCC 8th)) NSCLC patient treated with 2 cycles of anti-PD-1 immunotherapy combined with chemotherapy and anti-angiogenesis therapy; after two cycles of treatment, the patient achieved a partial response and obtained the opportunity for surgical treatment. After the operation, the patient achieved a pathological complete response and successfully transformed from unresectable stage IIIC lung cancer to radical surgery (ypT0N0M0). Our study is expected to provide new ideas for treating patients with unresectable stage IIIC NSCLC in the future.